Data and applications security and privacy XXX : 30th Annual IFIP WG 11.3 Conference, DBSec 2016, Trento, Italy, July 18-20, 2015. Proceedings /: 30th Annual IFIP WG 11.3 Conference, DBSec 2016, Trento, Italy, July 18-20, 2015. Proceedings. (2016) - Unknown
No abstract available